Can Kenya meet dairy production and greenhouse gas emissions reduction targets by 2030? - Oduor, Richard; Slater, Annabel; Arndt, Claudia; Graham, Michael (International Livestock Research Institute, 2024)
Kenya, like many African nations, faces the challenge of increasing dairy production to meet future demand while also reducing greenhouse gas (GHG) emissions, as population growth and dietary preferences shift towards greater consumption of animal products. While livestock production is a significant source of GHG emissions, it is also fundamental to achieving several other Sustainable Development Goals, including ending poverty, combating hunger and ensuring food security, promoting good health and well-being, and supporting decent work and economic growth. Efficient livestock production systems need to be identified to meet this challenge. However, there is a lack of local data on livestock productivity and GHG emissions, as well as knowledge on the effect of locally appropriate interventions on livestock productivity and GHG emissions.